Accountability and Political Competition - Braz Camargo; Arianna Degan (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2020)
Is increasing political competition good for voters? We study this question in the political career concerns framework. Our results show that the relationship between political competition, viewed as the cost of challenging incumbent politicians, and the politicians' incentive to behave in the voters' interest is undetermined. The same holds for the relationship between political competition and voter welfare, where selection of politicians into office also matters. In particular, voter welfare need not be maximized when challenging incumbent politicians is costless. So, unlike in economy markets, where increased competition is beneficial, in political markets increased competition can have adverse effects. We tie our results to a contractual incompleteness that is typical of political markets, namely, that the set of instruments available to discipline politicians' behavior is limited.
Keywords: 330